Bioclimatic assessment of abiotic factors affecting relative abundance and distribution of wheat stem sawfly (Hymenoptera: Cephidae) in western Canada. Issue 1 (26th September 2018) - Olfert, Owen; Weiss, Ross M.; Catton, Haley; Cárcamo, Héctor; Meers, Scott
Abstract: Wheat stem sawfly, Cephus cinctus Norton (Hymenoptera: Cephidae), indigenous to North America, quickly adapted from host native grasses to wheat crops ( Triticum Linnaeus (Poaceae)) with expansion of agriculture on the Great Plains of North America. Bioclimatic simulation tools, such as Climex, predict the potential geographic distribution and establishment of insects in ecosystems, based on climate. The ecoclimatic index, a measure of ecological suitability, integrates potential population growth with stresses to produce estimates of relative abundance. This simulation software was used to develop a bioclimate model for C. cinctus in western Canada. Results fostered a better understanding of how C. cinctus responded to selected climate variables. Two general circulation models were then applied to assess the response of C. cinctus populations to future climate. Relative to current climate, predicted changes in C. cinctus distribution and relative abundance were greatest for 2030, with a small further increase for 2070. Across the Prairies and Boreal Plains Ecozones, changes in ecoclimatic index were greater than in geographic distribution. Both general circulation models indicated most of this area would be categorised as very favourable. This suggests that the potential for pest populations could expand into areas that do not currently experience economic losses associated with C. cinctus .